2006
DOI: 10.1111/j.1399-0004.2006.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

LADD syndrome is caused byFGF10mutations

Abstract: Lacrimo-auriculo-dento-digital syndrome [LADD (MIM 149730)] is an autosomal-dominant multiple congenital anomaly disorder characterized by aplasia, atresia or hypoplasia of the lacrimal and salivary systems, cup-shaped ears, hearing loss, and dental and digital anomalies. Loss of function mutations in FGF10 were recently described in aplasia of the lacrimal and salivary glands [ALSG (MIM 180920; MIM 103420)] (Entesarian et al., Nat Genet 2005: 37: 125-127, Milunsky et al., American College of Medical Genetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 29 publications
2
121
1
7
Order By: Relevance
“…It has been hypothesized that ALSG results from haploinsufficiency of FGF10 whereas LADD syndrome is caused by a more complex mechanism involving residual activity derived from the mutant allele. However, this is contradicted by the finding by Milunsky et al 5 of a nonsense mutation in FGF10 in a mother with ALSG and her daughter with LADD syndrome. This variability in clinical expression is more likely to be explained by modifier gene loci such as FGFR2 and FGFR3 or, stochastic events.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…It has been hypothesized that ALSG results from haploinsufficiency of FGF10 whereas LADD syndrome is caused by a more complex mechanism involving residual activity derived from the mutant allele. However, this is contradicted by the finding by Milunsky et al 5 of a nonsense mutation in FGF10 in a mother with ALSG and her daughter with LADD syndrome. This variability in clinical expression is more likely to be explained by modifier gene loci such as FGFR2 and FGFR3 or, stochastic events.…”
Section: Discussioncontrasting
confidence: 49%
“…1 Two missense mutations have previously been reported in FGF10 and in both cases associated with LADD syndrome. 4,5 In this study, we report for the first time a FGF10 missense mutation associated with isolated ALSG. In family 1, a father and his son are affected by ALSG and they both carry an R80S substitution in FGF10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a significant number of LADD syndrome patients suffer from hearing defects [1]. In the adult brain (hypothalamus), expression of vivo [38] and we showed that FGF10 can translocate into the nucleus of these cells in vitro (Fig.…”
Section: Nuclear Translocation Of Fgf10 and Its Putative Functionsmentioning
confidence: 76%